Corporate credit growth determinants in Ukraine: Bank lending survey data application - Anatolii Hlazunov (Graduate Institute of International and Development Studies, 2023)
This study investigates the determinants of corporate lending in Ukraine with a focus on distinguishing between supply and demand factors. I use a two-step process to build a credit standards index (CSI) based on disaggregated data from the Ukrainian bank lending survey (BLS). This paper describes factors that are significant for corporate lending development in Ukraine. It contributes to the existing literature by developing a measure of corporate loan supply and analyzing its ability to explain corporate credit growth in Ukraine by using bank-level BLS data. First, I employ a panel ordered logit model to transform categorical data into a continuous index that measures the likelihood of credit standards tightening. Second, I examine how this index affects new corporate lending in both national and foreign currencies. I find that the credit standard index is influenced by exchange rate movements (with depreciations leading to tighter standards), bank liquidity, and bank competition. I also demonstrate that the CSI has a negative impact on corporate loans in national currency, with a more pronounced effect for smaller banks.
Keywords: G22; E44; C33; 330; supply and demand of corporate lending; bank lending survey data